Hubungan Tingkat Pengetahuan Terhadap Motivasi Ibu Hamil Trimester III Dalam Melaksakan Inisiasi Menyusui Dini Di Puskesmas Medan Denai - Amalia Farah Mutia Nur Hasibuan; Ika Nopa (Universitas Muhammadiyah Sumatera Utara, 2020)
Abstract: Early Breastfeeding Initiation (IMD / Inisiasi Menyusui Dini) is the firsttime a mother gives breast milk to her baby in the first 1 hour of birth. Theimplementation of Early Breastfeeding Initiation has several benefits, one ofwhich is to reduce infant mortality. However, the prevalence of theimplementation of Early Breastfeeding Initiatives in Indonesia is still very low.The purpose of the study was to determine whether there was a relationshipbetween the level of knowledge of the motivation of third trimester pregnantwomen in initiating early breastfeeding initiation at Puskesmas Medan Denai.The type of this study was the descriptive analytic study with the cross-sectionaldesign. The subjects in this study were third trimester pregnant women in thePuskesmas Medan Denai in August 2018, totaling 50 people. This researchtechnique uses purposive sampling and data analysis using the chi-square test.Retrieving data through filling in questionnaires. The results of the study showedthat there were 24 third trimester pregnant women who had sufficient level ofknowledge (48%) and third-trimester pregnant women who had strong motivationas many as 29 people (58%), the chi-square test results obtained p-value = 0.026.Conclusion,There is a relationship between the level of knowledge on themotivation of third-trimester pregnant women in initiating early breastfeeding atPuskesmas Medan Denai Keywords: Early Breastfeeding Initiation, Knowledge Level, Motivation